The new digital storytelling : creating narratives with new media - Alexander, Bryan, 1967- (Santa Barbara, Calif. : Praeger, 2011)
Explains the modern expression of the ancient art of storytelling, weaving images, music, text, audio, video, and music together. This book describes the narrative creation process with personal video, blogs, podcasts, digital imagery, multimedia games, social media, and augmented reality.
Includes bibliographical references and index.
Keywords: Interactive multimedia; Digital storytelling; Storytelling -- Data processing